2016
DOI: 10.5121/ijmit.2016.8201
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Mobile Banking in Saudi Arabia : An Emprical Evaluation Study

Abstract: This study explores the adoption of mobile banking practices in Saudi Arabia. It focuses on the existence of sufficient infrastructure, and the possible challenges that m-banking services may face. Also, discovers the potential opportunities in the country. A sample of banks in Saudi Arabia was surveyed via questionnaire, with a particular focus on the staff in the related IT departments. The findings demonstrate that although m-banking is believed to be important, there is a general lack of awareness, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…However, in relation to the issue of service quality, the EY GCC Digital Banking Report (2015) did not mention deficiencies relating to service quality. In another study, Alkhaldi (2016) indicated that the lack of a proper infrastructure has hampered the Saudi adoption of M-Banking on a wider scale. As such, insufficient networks in the Saudi countryside, the low rate of mobile diffusion to the banking sector, the modest mobile usage for distinctive bank services, and the insufficiency of necessary legal regulations, which aim to raise the service quality of M-Banking, constitute objective parameters that limit proper espousal of M-Banking in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in relation to the issue of service quality, the EY GCC Digital Banking Report (2015) did not mention deficiencies relating to service quality. In another study, Alkhaldi (2016) indicated that the lack of a proper infrastructure has hampered the Saudi adoption of M-Banking on a wider scale. As such, insufficient networks in the Saudi countryside, the low rate of mobile diffusion to the banking sector, the modest mobile usage for distinctive bank services, and the insufficiency of necessary legal regulations, which aim to raise the service quality of M-Banking, constitute objective parameters that limit proper espousal of M-Banking in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the aforementioned findings of Alkhaldi (2016), it can be seen that the study focused on service quality and system quality without focusing on issues related to information quality. Within this study, independent variables are service quality, information quality, system quality, performance expectancy, effort expectancy, hedonic motivation, social influence, price value, habit, and facilitating conditions, and the aforementioned variables impact on use (the dependent variable).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alabdan, 2017;Al-Ghaith et al, 2010;Al-Malkawi et al, 2016;Al-Somali et al, 2009;Awan et al, 2016) and m-banking in particular (i.e. Al-Husein and Sadi, 2015; Al-Jabri and Sohail, 2012, Alkhaldi, 2016Al-Otaibi et al, 2018;Alsheikh and Bojei, 2014;Hidayat-ur-Rehman, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, this study added perceived security and perceived privacy to the conceptual model due to their substantial roles in sensitive technological services that are related to financial dealings such as m-banking (e.g. Alabdan, 2017;Alkhaldi, 2016;Casalo et al, 2007;Finn et al, 2013;Khasawneh et al, 2018;Linck et al, 2006;Mashhour and Saleh, 2015).…”
Section: <Figure 1 About Here>mentioning
confidence: 99%